2018
DOI: 10.1111/apa.14274
|View full text |Cite
|
Sign up to set email alerts
|

Recent gestational diabetes was associated with mothers stopping predominant breastfeeding earlier in a multi‐ethnic population

Abstract: Recent gestational diabetes was associated with earlier cessation of predominant breastfeeding in Western European and non-Western women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…All ethnic minority groups were more likely to have unhealthier dietary pattern in pregnancy than European women, although the differences were largely explained by lower socioeconomic status and lower integration level in ethnic minority groups 45. South Asian women were also less likely to breast feed at 3 months postpartum than Western European women which may partly explain differences in weight retention 46. Furthermore, these findings from our cohort are supported by results from other studies conducted among ethnic minorities in Oslo.…”
Section: Discussionsupporting
confidence: 82%
“…All ethnic minority groups were more likely to have unhealthier dietary pattern in pregnancy than European women, although the differences were largely explained by lower socioeconomic status and lower integration level in ethnic minority groups 45. South Asian women were also less likely to breast feed at 3 months postpartum than Western European women which may partly explain differences in weight retention 46. Furthermore, these findings from our cohort are supported by results from other studies conducted among ethnic minorities in Oslo.…”
Section: Discussionsupporting
confidence: 82%
“…While the majority of babies in the study received breast milk during the first week, the proportion was less than in the general population in Norway 47. Studies do report differences in breast feeding initiation by maternal diabetes status and race 48 49. In addition, the breast feeding pattern in many South Asian and Middle East countries is characterised by late initiation of breast feeding and non-exclusive breast feeding 50 51.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the breastfeeding rates of GDM women are falling faster [ 7 – 10 ]. Several studies have reported that women with GDM have lower rates of breastfeeding and earlier interruption of breastfeeding in the first 6 months [ 11 , 12 ]. Study has shown that the main factors that hinder breastfeeding include maternal factors, social factors and work-related factors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%